Effect of polyvinylpyrrolidone ̶ polyethylene glycol blends on the corrosion inhibition of aluminium in HCl solution. Issue 5 (19th August 2014) - Umoren, Saviour; Eduok, Ubong M; Solomon, Moses M
Abstract : Purpose: The purpose of this paper is to investigate the effect of polyethylene glycol (PEG), polyvinyl pyrrolidone (PVP) and blended formulations on the corrosion inhibition of aluminium in HCl solutions at 30-60 oC and to study the mechanism of action. Design/methodology/approach: The inhibitive effect of the homopolymers and polymer blend were assessed using weight loss and hydrogen evolution methods at 30 and 60 oC. The morphology of the corroding aluminium surface without and with the additives was visualized using atomic force microscopy (AFM). The trend of inhibition efficiency with temperature was used to propose the mechanism of inhibition and type of adsorption Findings: Results obtained show that inhibition efficiency (η %) increases with increase in concentration of the polymers but decreases with increase in temperature. The inhibition efficiency of the homoploymers and their blends decreased with rise in temperature. Inhibition efficiency was found to be synergistically enhanced on blending the two homopolymers with highest inhibition efficiency obtained for (PEG: PVP) blending ratio of 1:3. The phenomenon of physical adsorption is proposed from the trend of inhibition efficiency with temperature. Research limitations/implications: The mechanistic aspect of the corrosion inhibition can be better understood using electrochemical studies such as potentiodynamic polarization and electrochemical impedance spectroscopy. Originality/value: Studies involving the use of polymer blends/mixtures as corrosion inhibitor for metals in corrosive environments is scarce. The results suggest that the mixture could find practical application in corrosion control in aqueous acidic environment. The data obtained would form part of database on the use of polymer-polymer mixtures to control acid-induced corrosion of metal.